Analyzing the Relationship between Perceived Educational Ethics and Thinking Styles of Students with Academic Enthusiasm: The Mediating Role of Academic Engagement - Hala Adnan Kazem Al-Adi; Hassan Ghalavandi; Behnaz Mohajeran (International Journal of Ethics and Society)
Introduction: Academic enthusiasm is one of the concepts of positive psychology in educational processes, which can increase under the influence of perceived educational ethics, thinking style and academic engagement. The present study was conducted with the aim of investigating the relationship between perceived educational ethics and thinking styles with students' academic enthusiasm, considering the mediating role of academic conflict. Material and Methods: The research method was descriptive correlation type with structural modeling approach. The statistical population included all the students of the fourth experimental high school of public schools in the center of Maysan city in the academic year 2023-2024 in the number of 1952 people, using Cochran's formula, 281 of them were selected by stratified random sampling. To collect research data, four standard questionnaires of perceived educational ethics, thinking style, academic engagement and academic enthusiasm were used. The face and content validity of the questionnaire was confirmed by experts and confirmed through factor analysis. The reliability of the instrument was confirmed using Cronbach's alpha coefficient. Data analysis was done using Pearson's correlation coefficient analysis and structural equation model in SPSS and Lisrel statistical software. Results: The results showed that the relationship between perceived educational ethics and thinking styles with academic enthusiasm is positive and significant. Also, the results showed that the mediating role of academic engagement in the relationship between perceived educational ethics and thinking styles with academic enthusiasm is positive and significant. Conclusion: Based on the results, it is possible to use the perceived educational ethics, thinking style and academic engagement in students to increase academic enthusiasm.